The influence of metformin and empagliflozin administration on gut microbiota in individuals with type 2 diabetes mellitus and hypothyroidism - K.A. Moskva; O.P. Kikhtyak; T.A. Kikhtiak; M.L. Farmaha; Y.L. Leshchuk; Y.S. Leshchuk (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. There is a lack of studies focusing on the combined impact of metformin, empagliflozin, and levothyroxine on the gut microbiota in patients with type 2 diabetes mellitus (T2DM) and hypothyroidism. The purpose of the study was to examine how the combination of metformin and empagliflozin affects gut microbiota composition in patients with type 2 diabetes and hypothyroidism. Materials and methods. We enrolled 47 patients who have been receiving hormone replacement therapy with levothyroxine at a stable dose over the past 2 years and were newly diagnosed with T2DM. All participants were divided into two groups and received either metformin alone or metformin plus empagliflozin for 6 months. Metabolic and hormonal parameters were measured before and after treatment, and stool samples were analyzed using PCR sequencing. Results. The study found that in both groups, there was an improvement in carbohydrate metabolism, lipid profile, and liver transaminases after treatment. The group treated with metformin plus empagliflozin had a more significant reduction in glucose, glycated hemoglobin, and atherogenicity coefficient than the group treated with metformin alone. We also found that combination therapy resulted in lower levels of Firmicutes and an increase in the number of Actinobacteria, as well as a higher ratio of Bacteroides fragilis to Faecalibacterium prausnitzii. Conclusions. The study shows for the first time that the combination of metformin, empagliflozin, and levothyroxine can directly affect the gut microbiota composition in patients with T2DM and hypothyroidism. These changes may be necessary for treating this cohort of patients and require further investigation.